A Conceptual Model of Aircraft Rescue and Fire Fighting (ARFF) Training Effectiveness for Enhancing National Aviation Safety - Alwazir Abdusshomad; Benny Kurnianto; Nawang Kalbuana (Jurnal Teknologi Kedirgantaraan, 2026)
Aviation safety serves as the fundamental pillar of the global aviation industry, with Aircraft Rescue and Fire Fighting (ARFF) personnel playing a critical role in managing emergency situations. Although the International Civil Aviation Organization (ICAO) has established global training standards, their implementation in Indonesia continues to face various challenges related to advancing aircraft technologies and increasing operational complexity. This study aims to formulate a holistic conceptual model to enhance the effectiveness of ARFF training programs in Indonesia by integrating international best practices and contextualizing them within national realities. Through a systematic literature review of scholarly publications, regulatory frameworks, and technical reports from 2015–2025, four key components of training effectiveness were identified: (1) Training Input, encompassing competency standards, psychologically based participant selection, and the availability of modern facilities; (2) Training Process, emphasizing the application of Competency-Based Training and Assessment (CBTA), simulation technology, and cross-functional exercises; (3) Training Output, assessing improvements in technical competence, stress management, and team coordination; and (4) Long-Term Outcomes, oriented toward enhanced emergency preparedness and reduced incident response time. The proposed model is expected to strengthen ARFF human resource capacity while reinforcing the national aviation safety ecosystem in a sustainable manner